Process conformance is associated with successful first intubation attempt and lower odds of adverse events in a paediatric emergency setting. Issue 9 (18th July 2019) - O'Connell, Karen J; Yang, Sen; Cheng, Megan; Sandler, Alexis B; Cochrane, Niall H; Yang, JaeWon; Webman, Rachel B; Marsic, Ivan; Burd, Randall
Abstract : Background: Intubation is an essential, life-saving skill but associated with a high risk for adverse outcomes. Intubation protocols have been implemented to increase success and reduce complications, but the impact of protocol conformance is not known. Our study aimed to determine association between conformance with an intubation process model and outcomes. Methods: An interdisciplinary expert panel developed a process model of tasks and sequencing deemed necessary for successful intubation. The model was then retrospectively used to review videos of intubations from 1 February, 2014, to 31 January, 2016, in a paediatric emergency department at a time when no process model or protocol was in existence. Results: We evaluated 113 patients, 77 (68%) were successfully intubated on first attempt. Model conformance was associated with a higher likelihood of first attempt success when using direct laryngoscopy (OR 1.09, 95% CI 1.01 to 1.18). The use of video laryngoscopy was associated with an overall higher likelihood of success on first attempt (OR 2.54, 95% CI 1.10 to 5.88). Thirty-seven patients (33%) experienced adverse events. Model conformance was the only factor associated with a lower odds of adverse events (OR 0.94, 95% CI 0.88 to 0.99). Conclusions: Conformance with a task-based expert-derived process model for emergency intubation was associated with a higher rate of success on first intubation attempt when using direct laryngoscopy and a lower odds of associated adverse events. Further evaluation of the impact of human factors, such as teamwork and decision-making, on intubation process conformance and success and outcomes is needed.